2006
DOI: 10.1148/radiol.2401050502
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Section CT in Patients with Cystic Fibrosis: Correlation with Peak Exercise Capacity and Body Mass Index

Abstract: In patients with CF, the correlation between thin-section CT score and exercise limitation is stronger than that between spirometry results or BMI and exercise limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 43 publications
1
33
0
5
Order By: Relevance
“…It has been more sensitive than FEV 1 for early detection of CF lung disease [5,23,24,[27][28][29][30]. HRCT detects structural airways damages, but its use has been restricted due to high levels of radiation exposure [57] and it has been suggested not to perform CT scans more than once every 2 or 3 years, especially in patients without respiratory symptoms [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been more sensitive than FEV 1 for early detection of CF lung disease [5,23,24,[27][28][29][30]. HRCT detects structural airways damages, but its use has been restricted due to high levels of radiation exposure [57] and it has been suggested not to perform CT scans more than once every 2 or 3 years, especially in patients without respiratory symptoms [3].…”
Section: Discussionmentioning
confidence: 99%
“…It can identify early and advanced structural damages [5,23,[27][28][29] that correlate with the disease severity and progression among CF patients [23,24,30]. Various methods have been used to quantify structural abnormalities [25,31].…”
Section: Introductionmentioning
confidence: 99%
“…38 Furthermore, in patients with CF the correlation between thin section computed tomographic (CT) findings of lung parenchymal damage and exercise limitation is stronger than that between spirometry results, or BMI and exercise limitation. 44 The CF genotype has also been reported to be related to exercise tolerance. 45 The aim of this study was to investigate if early The lung function data from the present study showed that FEV 1 , FVC, PEF and FEF were all significantly reduced in children with CCD compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that peak oxygen uptake determined during an incremental exercise test may better predict structural lung changes visible on thin-section CT imaging [44] and mortality [7] than FEV 1 or BMI, and that data from exercise testing may even provide information in addition to FEV 1 with respect to future decline in FEV 1 and hospitalizations [42]. …”
Section: Routine Monitoring and Evaluation Of Exercise-related Symptomsmentioning
confidence: 99%